Simulations and Modeling of Turbulence Flow Pattern in Pipe - Adetoyinbo, A. A.; Bello, A. K.; Omoliki, A. J. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This work is aimed at generating numerical simulations and modeling the turbulence flow pattern in pipes for water using Reynolds averaged Navier stokes equation. This is accomplished by using commercially available software called Cosmol Multiphysics in simulating and modeling the turbulence flow pattern of water in pipes at constant length but varying diameters of 0.16m, 0.15m, and 0.25m. The turbulence pattern was evaluated along the pipe by dividing the pipe into layers of 0.025m each. The turbulence pattern is found to be high in the middle of the pipe. The fluids at the boundary layer are found to have the same pattern for all the pipes.